Innovation in design, communication and engineering : proceedings of the 8th Asian Conference on Innovation, Communication and Engineering (ACICE 2019), October 25-30, 2019, Zhengzhou, P.R. China - Asian Conference on Innovation, Communication and Engineering 2019 : Zhengzhou, China); Lam, Artde Donald Kin-Tak; Prior, Stephen D. (Mechanical engineer); Shen, Siu-Tsen; Young, Sheng-Joue; Ji, Liang-Wen (Leiden, The Netherlands : CRC Press/Balkena, 2020)
This volume represents the proceedings of the 8th Asian Conference on Innovation, Communication and Engineering (ACICE 2019), which was held in P.R. China, October 25-30, 2019. The conference aimed to provide an integrated communication platform for researchers in a wide range of fields including information technology, communication science, applied mathematics, computer science, advanced material science, and engineering.The conference and resulting proceedings aim to enhance interdisciplinary collaborations between science and engineering technologists in academia and industry within this unique international network.
OCLC-licensed vendor bibliographic record.
Keywords: Telecommunication -- Asia -- Congresses; Computer engineering -- Asia -- Congresses; Technological innovations -- Asia -- Congresses; COMPUTERS / Computer Engineering; TECHNOLOGY / Electricity; TECHNOLOGY / Engineering / Civil